FACTORS IN DETERMINING THE PREFERENCE OF FAIR VALUE METHOD OF INVESTMENT PROPERTY - Yennisa, Yennisa; Juwiyato, Setya; Budiarto, Dekeng Setyo (Jurnal Akuntansi Kontemporer, 2020)
Financial Accounting Standard Statement in Indonesia is adopted from the IFRS by the IASB. IFRS applies those standards regarding the assessment of investment property as regulated in PSAK number 13. This research aims to determine the effect of leverage, firm size, asymmetry information, the difference in fair value gains, and share ownership on the selection of fair value investment property methods. This research is quantitative research with purposive sampling technique. The research was conducted on 69 companies listed on the Indonesia Stock Exchange in 2014-2017 with a total of 276 samples. The data analysis technique in this research used logistic regression analysis. The results indicate that firm size and asymmetry information influence the selection of the fair value method of investment property. The leverage, the difference in fair value profits, and share ownership do not affect. Based on the results of the research, there are still many firms that does not apply the fair value method because they prefer a more conservative accounting method. Additional costs regard to revaluation is one of the considerable factors why the firm resist to use the fair value method.